Melatonin: clinical prospects in immunology - Liadova, Tetiana; Popov, Mykola; Dorosh, Diana (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
Introduction. For a long time, HIV has been associated with a number of inflammatory, infectious and neoplastic skin diseases. In the era of anti-retroviral therapy researchers have found even more about the relationship between skin disease and chronic immunosuppression. In particular, clinicians continue to face the trend of difficult-to-control viral infections, chronic skin inflammation and itching in people living with HIV. Objectives. This article summarizes the latest updates in immunology, dermatology and HIV, revealing potential of the prospective substance melatonin and its efficacy in treating herpesvirus skin diseases as an alternative immunomodulator. Materials and methods. A comprehensive literature search was carried out in July 2020 using electronic databases PubMed, EMBASE, MEDLINE, U.S. National Library of Medicine Clinical Trials, ResearchGate, and Cocharane Library. Results. This review includes 24 articles, that demonstrated the modulating properties of melatonin and have established its effectiveness in the treatment of diseases associated with immunodeficiency conditions. Melatonin has been shown to have a regulatory effect on the immune system and directly enhance the immune response by improving the proliferation and maturation of natural killers, T and B lymphocytes, granulocytes and monocytes, and activates complement receptors. Conclusions. Currently, the course of dermatological manifestations associated with herpes viruses, unfortunately, remains unfavorable and persists with high mortality coefficients, so the development of new approaches to the provision of medical care to HIV-infected patients is still relevant. Recent scientific studies indicate the high effectiveness of melatonin in the treatment of diseases accompanied by immunodeficiency. Researching of its effects in the dermatological manifestations of herpesvirus infections on the background of HIV is prospective and necessary for expand drug provision, treating comorbid conditions and improving the quality of life of each patient.